Analysis of the Education Levels Role and Community Understanding of Vegetation Patterns for Private Green Spaces in Settlement Areas - Dienny Redha Rahmani; Dina Rafidiyah (Green Visioneers, 2018)
Private Green Spaces have become a necessity for residential areas. However, it requires initiative from the community itself to provide it, while the initiative comes from understanding the community. This study needs to be done in order to analyze the vegetation patterns of private green spaces formed based on the level of education and people's understanding of the green space. The data needed in this study is divided into two, namely the understanding of the community and the vegetation patterns of private green spaces. Understanding the community is obtained from the level of education and community preferences regarding private green spaces. The vegetation pattern is the actual condition in the private green space of the community. The results obtained show that the level of education influences people's understanding and the actual conditions of the private green space of the community. But in general, it turns out that most people have a good understanding of the existence of a private green space. The pattern of vegetation in the private green spaces are in accordance with the requirements for the existence of the private green spaces.